IMPACT OF CHEMICAL MUTAGENESIS USING ETHYL METHANE SULPHONATE ON CASTOR SEED GERMINATION AND SEEDLING VIGOUR - V. DINESH KUMAR and S.J. RAHMAN, K. GREESHMA, G. UMA DEVI, R. DURGA PRASAD, S. SENTHILVEL (The Journal of Research, PJTSAU, 2023)
Mutations are the primary source of all genetic variations existing in any organism, including plants. EMS-induced mutation is a highly successful strategy for developing superior crop varieties and it is widely employed in crop breeding. To the optimum conditions for mutagen treatment, the seeds of castor genotype DCH-519 was soaked in water for 24 h. The pre-soaked seeds were treated with the chemical mutagen, Ethyl Methane Sulphonate (EMS) with four different concentrations (0.25%, 0.5%, 1.0%, 1.5%)at four different time durations (4, 8, 12, 16 h).The effect of treatment on germination, seedling length, seedling vigour index- I (SV-I) and seedling vigour index -II (SV-II) was studied. It was observed that the germination percentage, speed of germination,seedling length and seedling vigour index decreases with increasing concentrations of EMS.The LD50(Lethal dose) value wasdetermined based upon the seed germination percentage.